FAKTOR – FAKTOR YANG MEMENGARUHI RENDAHNYA PENGGUNAAN KONTRASEPSI IUD - Novica Jolyarni D; Rika Handayani; Nailatun Nadrah (Jurnal Keperawatan Priority, 2023)
The IUD is a modern contraceptive designed in such a way as to its size, material, and active period. Then placed in the uterine cavity as a contraceptive effort to prevent fertilization and stop the egg from implanting in the uterus. This study aimed to determine the distribution of frequencies, relationships, and factors that were more dominant, namely age, education, knowledge, attitudes, and husband's support for IUD contraception. The type of this research was an analytic survey with a cross-sectional approach; the population in this study was 171, namely all mothers who did not use IUD contraception in the Rantauprapat City Health Center. working area Data analysis used univariate, bivariate with a chi-square test, and multivariate with a logistic regression test. The results of the study using the chi-square test were seen from the results of age (p-value) = 0.001, <0.05. Knowledge (p-value) = 0.000 <0.05 and attitude (p-value) = 0.003 <0.05. Then there is the influence of age, knowledge, and attitudes with the low use of IUD contraception and the most influential attitude factor seen from the results of multivariate analysis with a regression test value of <0.25. The conclusion of this study is that there is an influence of age, knowledge, and attitudes toward the use of IUD contraception in the working area of ​​the rantauprapat city health center. It is hoped that health workers, especially midwives, will be more active in promoting types of contraception, especially regarding IUD contraception.